2016
DOI: 10.1007/s10096-016-2672-2
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus colonization related to severity of hand eczema

Abstract: Knowledge on Staphylococcus aureus colonization rates and epidemiology in hand eczema is limited. The aim of this study was to clarify some of these issues. Samples were collected by the "glove juice" method from the hands of 59 patients with chronic hand eczema and 24 healthy individuals. Swab samples were taken from anterior nares and throat from 43 of the 59 patients and all healthy individuals. S. aureus were spa typed and analysed by DNA-microarray-based genotyping. The extent of the eczema was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 39 publications
(50 reference statements)
6
32
1
3
Order By: Relevance
“…In contrast, the skin microbiome of AD patients was highly over-represented by Staphylococcus (S.) aureus which allowed the discrimination of a S. aureus "low" and "high" colonized state. The latter one was shown to be paralleled by increased barrier dysfunction (e.g., CLDN8, FLG) and a stronger immune cell related profile (e.g., IL13, IL5) [148,151]. This identified "high" colonized state may also be more prone to HSV-1 infections as it is seen in ADEH+ patients [88].…”
Section: Disease Subgroupingmentioning
confidence: 91%
“…In contrast, the skin microbiome of AD patients was highly over-represented by Staphylococcus (S.) aureus which allowed the discrimination of a S. aureus "low" and "high" colonized state. The latter one was shown to be paralleled by increased barrier dysfunction (e.g., CLDN8, FLG) and a stronger immune cell related profile (e.g., IL13, IL5) [148,151]. This identified "high" colonized state may also be more prone to HSV-1 infections as it is seen in ADEH+ patients [88].…”
Section: Disease Subgroupingmentioning
confidence: 91%
“…Patients with HE due to or aggravated by work-related exposures may have to change job or modify working routines to reduce the burden on the skin. More than half of all HE patients are colonized by bacteria (Staphylococcus aureus), 3,4 the risk of colonization being strongly related to severity of the disease. This creates a problem for individuals working with food where contamination is a risk, and for individuals working in the healthcare sector, where transmission of bacteria to patients may be a consequence.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare workers, especially nurses, nursing auxiliaries, and hospital cleaning staff, often bear the maximum burden of occupational contact dermatitis, owing to frequent “wet work” and daily contact with both irritants and allergens, leading to chronic absenteeism, increased health costs, and an impaired quality of life (QoL) . Hand eczema may also lead to increased carriage of hazardous microorganisms, making it a potential route for transmission of infection …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Hand eczema may also lead to increased carriage of hazardous microorganisms, making it a potential route for transmission of infection. 6 The prevalence of hand eczema among hospital workers in countries other than India ranges from 6% to 80%. [7][8][9][10][11][12][13][14][15][16][17][18] However, most studies on hand eczema have been based on self-reported surveys, and have utilized varied outcome measures, and almost no epidemiological data on hand eczema among healthcare workers exist in India.…”
Section: Introductionmentioning
confidence: 99%